Antykonkurencyjne innowacje – oksymoron czy realne wyzwanie prawa antymonopolowego? - Molski, Rajmund (Wydawnictwo Naukowe UAM, 2017)
One of the overriding principles of modern economic policy is promotion of innovation. It also turns out, however, that innovations may work against competition, thus becoming a major challenge for antitrust law. The importance and the degree of diffi culty surrounding this challenge as well as some controversies related to it can be evidenced by the antitrust enforcement policy referring to innovations. This policy has thus far been highly enigmatic and labile. It seems that no consensus can be reached on the relation between competition and innovations as much as it cannot be achieved on the validity of including the latter in the antitrust enforcement regime, particularly when it comes to applying the prohibition of the abuse of a dominant position. While it is true that innovations compound the risk of antitrust errors, especially those consisting in de-legalisation of innovations which are not anticompetitive, it would nevertheless be wrong to underestimate, and even more so to ignore, the risk of errors amounting to an unjustiﬁ ed tolerance of anticompetitive innovations and an overstated belief in the self-regulatory ability of the market. In any case, considering the priority objective of the economic policy which should be to support and promote innovations, as well as taking into account that the goal of antitrust law is not only to settle real conﬂ icts arising between innovations and the protection of competition, but also to provide for an innovation-friendly environment, the antitrust intervention into innovations should be sensible, farsighted and predictable. Otherwise, antitrust law may become a burden for the actual and potential innovators – like the mythical sword above the head of Damocles.
Anticompetitive innovations – oxymoron or a real challenge for antitrust law?
Keywords: anticompetitive innovations; unilateral conduct restricting competition; antitrust law